Foreword - Michelle Sanson (Legal Education Review)
Research on the ‘first-year experience’ of law students has generally focussed on the social and academic support needs of school leavers making the transition to tertiary study. However, as increasing numbers of law schools now offer a Juris Doctor (JD), or a ‘graduate-entry’ law degree, there is a corresponding need to understand and support the ‘first-year experience’ of students who commence study in law as postgraduates. To contribute to the knowledge base on the JD first year experience, this paper provides an overview of first-year measures developed and implemented in the Melbourne Law School’s JD program over a four-year period, 2008–2011. The focus is on identifying practical examples of effective first-year strategies that may be adapted and refined, as appropriate, in other JD programs. The authors argue that, while the transition issues and first-year experiences of graduate law students are not identical to those of undergraduate LLB students, there is a similar need to design a first-year graduate program in law that intentionally: engages students in learning and skill development; provides timely academic and wellbeing support; and creates a sense of belonging and connectedness.